Detection of the dog/coyote variant of rabies virus in the Mexico-US border - Jaramillo, E.; Villareal, J. Z.; Galindo, E. I.G.; Carranza, P.; Meléndez, A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Currently in the border states of northern Mexico, samples from skunks and dogs that have the V-1 antigenic variant of the rabies virus have been identified, however, genetic analysis indicates that they are strains of skunks. In 2010, 4 cases of human rabies were registered in Mexico, while in Nuevo Leon there was 1 case of canine rabies transmitted by insectivorous bats. It has been almost a decade since the apparent non-transmission of the (V-1) variant dog/ coyote, in the border between Mexico (Coahuila and Tamaulipas) and USA (Texas). Surveillance data suggest that this variant of canine rabies virus is not longer in circulation in the United States of America, however, the last detection was registered in March 2004 in the US-Mexico border. In addition, one dog carrying the rabies virus was detected in June 2011 in the town of Sabinas Hidalgo, NL., which is about 130 km from the US-Mexico border. This finding is very important because the (V-1) variant (dog/coyote) could be present on the border of both countries. The geography of this region is very similar to Texas, which may permit the free movement of carnivorous species on both sides of the border. Therefore, the objective of this study was to identify the (V- 1) variant of rabies virus in the dog from Sabinas Hidalgo, NL. By using direct immunofluorescence, antigenic characterization with a panel of 8 monoclonal antibodies, RT-PCR and nucleotide sequencing techniques, the 709pb (751nt to 1460nt) and 420pb (992nt to 1411nt) fragments from the semi-variable region of the viral N protein were analyzed. According to the antigenic characterization, the variant found was the V-1, while the molecular study was also positive for this variant. Our results suggest the same lineages published by Velasco-Villa et al., 2005 in the analyzed sample. This study demonstrates the actual prevalence of the V-1 variant (dog/coyote) in the US-Mexico border and warns about the risk for transmission of the V-1 variant to humans, as well as to domestic and wild animals. Acknowledgements: We are grateful to Miguel Angel Zuniga, Isabel Aguilar Tavitas and Alma Liliana Lizarán Meneses for their support in the diagnosis of rabies virus. Financial support: This work was supported by the Rabies Program of the Ministry of Health of Nuevo Leon and Health Services of Nuevo Leon.